A Pan-Cancer Analysis of the Oncogenic and Immunogenic Role of m6Am Methyltransferase PCIF1 - Jin, Ming-Zhu; Zhang, Yi-Gan; Jin, Wei-Lin; Wang, Xi-Peng (Frontiers in Oncology, 2021)
Background Phosphorylated CTD-interacting factor 1 (PCIF1) is identified as the only known methyltransferase of N6,2′-O-dimethyladenosine (m6Am) in mRNA. However, its oncogenic and immunogenic role in cancer research is at an initial stage. Methods Herein, we carried out a pan-cancer analysis of PCIF1, with a series of datasets (e.g., TIMER2.0, GEPIA2, cBioPortal). Results PCIF1 expression was higher in most cancers than normal tissues and was discrepant across pathological stages. Highly expressed PCIF1 was positively correlated with overall survival (OS) or disease-free survival (DFS) of some tumors. PCIF1 expression had a positive correlation with CD4+ T-cell infiltration in kidney renal clear cell carcinoma (KIRC), CD8+ T cells, macrophages, and B cells in thyroid carcinoma (THCA), and immune checkpoint genes (ICGs) in LIHC but a negative correlation with CD4+ T cells, neutrophils, myeloid dendritic cells, and ICGs in THCA. It also affected tumor mutational burden (TMB) and microsatellite instability (MSI) of most tumors. Conclusion PCIF1 expression was correlated with cancer prognosis and immune infiltration, suggesting it to be a potential target for cancer therapy.